2019
DOI: 10.1007/s10552-019-01150-w
|View full text |Cite
|
Sign up to set email alerts
|

Educating Latinas about cervical cancer and HPV: a pilot randomized study

Abstract: Introduction-The purpose of this study was to assess effects of three different educational intervention arms on knowledge of and intention to receive Pap testing and HPV co-testing. Methods-Three active educational intervention arms were developed: a fotonovela, a radionovela, and a digital story. A pilot randomized controlled trial (RCT) of 160 Latinas was conducted to assess the effectiveness of the intervention arms in increasing knowledge of cervical cancer and HPV and intention to be screened for cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 41 publications
(36 reference statements)
0
25
0
1
Order By: Relevance
“…Women’s knowledge and educational interventions prevent HPV transmission, increase the acceptability of HPV vaccine, and thus help to improve HPV vaccine coverage [ 59 , 60 , 61 , 62 ]. Video education has been reported to increase the willingness to accept the HPV vaccine by about 20% in young women [ 61 ].…”
Section: Effects That Influence the Vaccine Coverage And Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Women’s knowledge and educational interventions prevent HPV transmission, increase the acceptability of HPV vaccine, and thus help to improve HPV vaccine coverage [ 59 , 60 , 61 , 62 ]. Video education has been reported to increase the willingness to accept the HPV vaccine by about 20% in young women [ 61 ].…”
Section: Effects That Influence the Vaccine Coverage And Efficacymentioning
confidence: 99%
“…Video education has been reported to increase the willingness to accept the HPV vaccine by about 20% in young women [ 61 ]. Educational videos, outlining the risks of HPV and the benefits of vaccines have been shown to be an efficient way to improve vaccination behaviors [ 59 , 60 ]. In addition, a randomized trial with 30 pediatric and family medicine clinics showed that presumptive announcements led to a 5% increase in HPV vaccine coverage compared to control clinics [ 63 ].…”
Section: Effects That Influence the Vaccine Coverage And Efficacymentioning
confidence: 99%
“…A total of six studies were included in this review and represented various ranges of estimated age-standardized incidence rates (ASR) of cervix uteri carcinoma from the International Agency of Research on Cancer GLOBOCAN 2022 [36]. Three studies conducted in the US, a developed country, had ASR of < 7.0 per 100 000 [11,37,38]. Two studies from African LMICs, i.e.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, almost 90% of deaths occurs in the developing countries and low-to middle-income countries (LMICs), which are less successful in implementing screening methods [1,2,9]. Currently, the developed countries use electronic health (e-health) interventions and media campaigns as an education method as a strategy to reach more women to promote CC screening [10][11][12][13]. Therefore, investing in e-health promotion programs might enable the cultivation of knowledge on the benefits of CC screening and promote lifelong screening for preventing CC.…”
Section: Introductionmentioning
confidence: 99%
“…Em sua pesquisa Thompson et al (2019) avaliou os efeitos de três diferentes braços de intervenção educacional sobre o conhecimento e a intenção de realizar o teste de Papanicolau e do co-teste de HPV. As latinas em todos os grupos participantes Research, Society andDevelopment, v. 10, n. 13, e305101321268, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i13.21268 deste projeto tinham altos níveis de conhecimento básico sobre o risco de câncer cervical.…”
Section: Lilacs Bdenf -Enfermagemunclassified